Case report: Severe hepatic fibrosis induced by chronic cholestasis of congenital biliary dilation treated by laparoscopic surgery after immunonutrition support– An infantile case - Sugita, Koshiro; Onishi, Shun; Muto, Mitsuru; Nishida, Nanako; Nagano, Ayaka; Murakami, Masakazu; Harumatsu, Toshio; Yamada, Koji; Yamada, Waka; Kawano, Takafumi; Ieiri, Satoshi (Frontiers in Pediatrics, 2023)
Introduction: In some patients with congenital biliary dilation (CBD), biliary cirrhosis has been reported to rapidly progress from the neonatal period to the infantile period. We herein report an infantile case of CBD that showed severe biliary cirrhosis at the diagnosis, which was treated by laparoscopic surgery. Case presentation: A 16-month-old girl underwent conservative therapy for liver dysfunction and cholangitis on a remote island of our prefecture. She was transferred to our hospital after the detection of a huge dilated common bile duct on imaging at the previous hospital. Contrast-enhanced computed tomography showed a dilated common bile duct (maximum diameter: 5 cm), thus suggesting CBD. However, her laboratory data on admission showed a poor nutritional status and severe liver dysfunction (Total protein, ** mg/dL; Alb, 2.5 mg/dL; AST, 79 IU/L; ALT, 43 IU/L; γ-GTP, 491 mg/dL; D-bil, 0.3 mg/dL; CHE, 90 IU/L; NH3, 123 μg/dL). We initially performed laparoscopic exploration and bile drainage via the gallbladder, noting severe hepatic fibrosis resembling end-stage liver cirrhosis. After placing a drainage tube in the gallbladder, cholangiography was performed. Cholangiography showed Todani type IVa CBD with pancreaticobiliary maljunction. Contrast agent flowing into the duodenum could not be confirmed. The patient received liver-supporting therapy and nutritional support for 7 weeks before definitive surgery. Following the improvement of the hepatic synthetic capacity (TP, ** mg/dL; Alb, 4.0 mg/dL; AST, 82 IU/L; ALT, 78 IU/L; γ-GTP, 157 mg/dL; D-bil, 0.2 mg/dL; CHE, 232 IU/L; NH3, 75 μg/dL), we performed extrahepatic bile duct excision and hepaticojejunostomy laparoscopically. Laparoscopic surgery was successfully performed along with liver biopsy. Histopathologically, the liver specimen showed chronic hepatitis and fibrosis (F3A2). Biliary scintigraphy showed good bile excretion at postoperative day 15. The postoperative course uneventful, and the patient was discharged on the 23rd day after surgery. A needle liver biopsy six months later showed mild improvement of chronic hepatitis and fibrosis (F2-3A1). The patient was regularly followed at the outpatient clinic. Conclusions: Severe liver fibrosis was suspected to be continuous cholestasis of CBD after birth. Chronic cholestasis of CBD can lead to end-stage liver fibrosis requiring liver transplantation.